El trabajo colaborativo para el desarrollo de las relaciones interpersonales en el proceso de la inclusión - Moreira Velásquez, Osmar Alejandro (2023)
The present study details the variables of collaborative work and development of interpersonal relationships, the central problem is the need to have a support resource on how to integrate collaborative work in the 7th GEB parallel "A" classroom, the proposed objective was: Analyze the collaborative work for the development of interpersonal relationships in the inclusion process in the boys and girls of 7th GEB parallel "A" of the morning session of the Basic Education school "Héroes de Paquisha". The methodology used was descriptive, not experimental with the use of the deductive method, the instruments applied were the survey and the interview with a sample of 20 students, 1 teacher and 1 manager; The results obtained showed that, of 100% of the observed students of the "Héroes de Paquisha" Basic Education School, 45% of the students have the initiative to work as a team with new classmates, while 30% sometimes, and 25% have no initiative to work as a team with new colleagues. The conclusions reached showed that inclusion must currently be considered as part of the teaching practice within educational institutions, but above all, knowledge must be expanded and it must be a fundamental requirement that all teachers must have through educational strategies applicable in a didactic way through activity guides that direct the work that is carried out daily with the students that will allow to increase the levels of education at the local level and visions to be an example for other educational institutions.